Multi-user shortwave data link algorithm based on multi-domain orthogonal frequency selection - LI Lin, HUANG Xuexiao, PENG Xiaoyong (Zhihui kongzhi yu fangzhen)
A multi-user shortwave data link algorithm based on multi-domain orthogonal frequency selection is proposed to address the difficulties in frequency selection, low timeliness, susceptibility to interception and interference during the fixed frequency construction of shortwave data link, as well as the problem of mutual interference during the multi-user simultaneously building the link. Firstly, the algorithm segments the frequency bandwidth using multi-domain orthogonal planning based on the number of users and frequency interval, and then obtains the set of available frequency points for each user based on the disabled frequency and frequency demand. Finally, the system frequency-selecting chain building function is used to establish the links for multiple users simultaneously. The algorithm effectively solves the problems of frequency selection difficulty, frequency conflict, link instability, and frequency exposure in multi user simultaneous chain building, effectively improving system availability and anti-interference ability.